2019
DOI: 10.1108/ejim-07-2018-0155
|View full text |Cite
|
Sign up to set email alerts
|

An audit of innovation drivers: some empirical findings in Greek agri-food firms

Abstract: Purpose The purpose of this paper is to develop a conceptual model and examine the relevance of a set of five dynamic drivers to building and sustaining the innovation capability of agri-food firms. Design/methodology/approach The empirical data were acquired through a recent study of 436 Greek agri-food firms. Regression analysis was employed to examine the correlation between innovation drivers and each of the four innovation capability dimensions, namely, product innovation, process innovation, organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 89 publications
0
14
0
3
Order By: Relevance
“…Thus, the innovation strategies which are effective in improving firm performance in certain environments may not be as effective as they are in other business environments (Tsai and Yang, 2013). Kafetzopoulos and Skalkos (2019) support the view that organizations may attempt to improve innovation capability by adopting appropriate strategies that enable them to manage environmental uncertainties. Implementing strategies to reduce critical internal and external contingencies may represent a response strategy by management to achieve innovation and business outcomes.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, the innovation strategies which are effective in improving firm performance in certain environments may not be as effective as they are in other business environments (Tsai and Yang, 2013). Kafetzopoulos and Skalkos (2019) support the view that organizations may attempt to improve innovation capability by adopting appropriate strategies that enable them to manage environmental uncertainties. Implementing strategies to reduce critical internal and external contingencies may represent a response strategy by management to achieve innovation and business outcomes.…”
Section: Introductionmentioning
confidence: 77%
“…The main motivation of this study is therefore to propose a novel two-staged approach combining artificial neural networks (ANN) and random forests (RF), which overcome previous traditional regression models (see e.g. [20][21][22]), in terms of accuracy and ability to capture more complex relationships and to handle nonlinear and hierarchical behaviours [23]. It could help us to reveal not the effects of innovation determinants on firms´innovation performance but the importance of innovation determinants within innovation processes.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the researchers and scholars in this article used the medium sample size from 436 samples (Kafetzopoulos & Skalkos, 2019); 340 samples (Donkor et al, 2018) in view of Hair et al (2006) to small sample size (115 samples) (Abdulai Mahmoud & Hinson, 2012) for factor analysis, linear regression analysis by SPSS software. In addition, causal/causal model analysis by partial least squares PLS (Latan & Ghozali, 2012) has been investigated by many researchers.…”
Section: Research Methodology and The Relationship Between Innovation Capacity And Firm Performancementioning
confidence: 99%
“…Production innovation capacity and process innovation capacity were also studied together (Wahyuni & Sara, 2020). Most studies have identified and recognized innovation capacities through a combination of innovation capacity including product innovation, process innovation, organizational innovation, and marketing innovation (De Martino & Magnotti, 2018;Kafetzopoulos & Psomas, 2015;Kafetzopoulos & Skalkos, 2019;Rajapathirana & Hui, 2018). One study suggested that management innovation is the essential action and capability to implement innovation of any organization (Maldonado-Guzmán, Garza-Reyes, Pinzón-Castro, & Kumar, 2019); divided innovation capacity into radical and incremental (Al-Ansari, Pervan, & Xu, 2013; Lewrick, Chen, Raeside, & Omar, 2012).…”
Section: Concept and Classification Of Innovation Capacitymentioning
confidence: 99%
See 1 more Smart Citation